Aktivitas Selulolitik dan Xilanolitik Enzim Sampah untuk Biobleaching Pelepah Batang Pisang - Solikhatiningsih, Solikhatiningsih (Universitas Airlangga, 2015)
This research aims to study the cellulolytic and xylanolytic activity of garbage enzyme. The garbage enzyme was prepared by fermentation of garbage parts of fruits, and vegetables, brown sugar and water in a weight ratio of 3: 1: 10 (w/w) for 3 months. Cellulolytic and xylanolytic activities were assayed toward CMC and xylan as substrates respectively. The reducing sugar was determined using DNS method. The garbage enzyme showed cellulose activity of 3.83 U/ml and xylanase activity of 5.66 U/ml. The biobleaching was initiated by boiling the dried stem of banana bunch in buffer pH 8 for 3 hours. The biobleaching process was performed at various concentration of garbage enzyme: 0, 5, 10, 15, 20, 25, 30, 35 and 40 % (W/V). The mixture of enzymatic reaction was incubated at 40 oC for 2 hours. The pulps were characterized of the water, cellulose, hemicellulose and lignin contents, whiteness, tensile index, tear index and its morphology. The result of this study showed that the addition of 20% garbage enzyme in biobleaching of stems of the banana bunch improved the pulp whiteness of 4.87%. Characteristics of pulps obtained were in accordance with ISO standards SNI-14-0091-1998 as raw material for paper pulp.Keywords: garbage enzyme, cellulase, xylanase, biobleaching, stems of the banana bunch